Evaluating the Rutting Resistance of Modified Hot Mix Asphalt (MHMA) with Palm Leaves Fibers (PLFs) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
High temperatures, high axle loads, and low-quality paving material can all contribute to the distress of rutting in flexible pavement. This paper investigates adding palm leaf fibers (PLF) to hot mix asphalt (HMA) to improve its resistance to rutting. In order to make Modified HMA (MHMA) by employing Modified Dry Process (MDP), which was prepared by adding small balls to HMA, HMA mixes were prepared with traditional mineral filler and Hydrated Lime. PLF was added at dosages of 2%, 4%, and 6% of aggregate weight. A Wheel Track device linked to a computer system monitored rutting depth as a sign of rutting resistance, and Marshall tests were also performed to assess stability and flow characteristics. According to the findings, PLF considerably increased rutting resistance throughout. The use of PLF found to be highly effective in improving rutting resistance at all dosages; the highest results were obtained at 6%. This implies that sustainable paving technologies could displace traditional techniques.